Banff, jasper & glacier national parks travel guide ebook - Planet, Lonely (National Parks., 2012)
'Lonely Planet guides are, quite simply, like no other'. New York Times The ultimate, most comprehensive guide to travelling in Banff, Jasper & Glacier National Parks includes up-to-date reviews of the best places to stay, eat, sights, cultural information, maps, transport tips and a few best kept secrets – all the essentials to get to the heart of Banff, Jasper & Glacier National Parks . This guide is the result of over in-depth research by two dedicated authors and local experts who immersed themselves in Banff, Jasper & Glacier National Parks , finding unique experiences, and sharing practical and honest advice, so you come away informed and amazed. Regions covered: Banff National Park, Jasper National Park, Glacier National Park Inside Lonely Planet Banff, Jasper & Glacier National Parks : • Full color styling and images • Clear, easy-to-read color maps • A brilliant new page layout for fast and hassle-free reading while on the go • Itineraries organized by region or length of trip • Up-to-date recommended points-of-interest – covering eating, sleeping, going out, shopping, activities and attractions • In-depth features to uncover the world's iconic sights • Hundreds of money saving tips • Our latest trip planning tools to help you get around smoothly • Additional sections including Wildlife, Conservation and more. Special eBook enhancements • Scalable maps – enabling you to zoom in for greater detail • Comprehensive interlinking – enabling you to seamlessly flip between pages, jump between maps and reviews, or visit the websites of places we recommend • Search – go straight to what you are looking for with the inbuilt search capability • Add notes – touch a word to add notes and personalize your guidebook • Bookmark – use bookmarks to quickly return to a page • Dictionary – look up the meaning of any word • Plus pinch and zoom images and scalable font size Written and researched by Oliver Berry and Brendan Sainsbury.